Development of a microwave stunning system for cattle 2: Preliminary observations on behavioural responses and EEG. (February 2019) - Small, A.; Lea, J.; Niemeyer, D.; Hughes, J.; McLean, D.; McLean, J.; Ralph, J.
Abstract: DTS: Diathermic Syncope® (DTS) is a novel system for rendering animals insensible prior to slaughter, utilizing microwave energy to induce a rise in temperature in the brain to a point at which the animal is expected to lose consciousness. During development and optimisation of the system, two trials were carried out utilizing non-anaesthetized adult cattle, to gather data on behavioural outcomes and EEG changes following energy application. In trial1, ten cattle received DTS treatments (high energy >290 kJ, n = 3; low energy <200 kJ, n = 4; and intermediate 200 < 290 kJ, n = 3), and seven received captive bolt stunning, prior to exsanguination. In trial 2, following improvements to the efficiency of energy delivery, 20 cattle received DTS (200–360 kJ). Post treatment EEG was characterized by seizure-like activity and reductions in 95% spectral edge and median frequencies; with EEG suppression persisting for at least 80 s up to over 4 min post treatment application. Animals showed: Loss of posture, Loss of corneal responses; Loss of withdrawal response (pinprick); Eye staring, not following movement. The animals remained unresponsive to stimuli for up to 4 min post DTS, and behavioural expression of distress was not observed. Seventeen of the 30 animals showed indications of returning reflex responses after 100 s post treatment, suggesting that animals receiving lower energy applications may recover from the stun. Highlights: Microwave energy was used to stun cattle. Insensibility lasted long enough to allow humane exsanguination. EEG suppression persisted for at least 80 s and up to 4 min. Corneal reflex was absent for at least 100 s. Behavioural response was similar to an epileptiform seizure.